Not playing the game : sport and Australia's great war. - Fowler, Xavier (Melbourne University Press, 2021)
"War remembrance and sport have become increasingly entwined in Australia, with AFL and NRL Anzac Day fixtures attracting larger crowds than dawn services. National representative teams travel halfway around the world to visit battle sites etched in military folklore. To validate their integration into this culturally sacred occasion, promoters point to the special role of sport in the development of the Anzac legend, and with it, the birth of the nation. The air of sombre reflection that surrounds each Anzac Day is accompanied by a celebratory nationalism that sport and war supposedly embody. But what exactly is being remembered, and indeed forgotten, in these official commemorations and tributes? In Not Playing the Game, Xavier Fowler reveals that the place of sport in the Great War was highly contested. Civilian patriots and public officials complained that spectator sport distracted young men from enlisting and wasted public finances better spent elsewhere. Sport's defenders argued it was a necessary escape for a population weary of the pressures of war. These competing views often reflected differences of class, politics and ethnicity, and resulted in ferocious, sometimes violent, clashes. Not Playing the Game challenges the way our memories of the war are influenced by the fervour of sport, painting a picture not of triumph but immense turmoil and tragedy."--OverDrive.